Good publication practice for communicating company sponsored medical research: the GPP2 guidelines. (29th November 2009) - Graf, Chris; Battisti, Wendy P; Bridges, Dan; Bruce-Winkler, Victoria; Conaty, Joanne M; Ellison, John M; Field, Elizabeth A; Gurr, James A; Marx, Mary-Ellen; Patel, Mina; Sanes-Miller, Carol; Yarker, Yvonne E; et al.
Abstract : In response to changes in the environment in which authors, presenters, and other contributors work together to communicate medical research the International Society for Medical Publication Professionals has updated the good publication practice guidelines